Institutional Revitalization: Synchronizing Local Legislative Programs with Local Government Work Plans in Gorontalo, Indonesia - Tulie, Espin; Aneta, Asna; Aneta, Yanti; Sulila, Ismet (Indonesian Association for Public Administration (IAPA), 2024)
This study examines the topic of Institutional Revitalization: Realizing the Synchronization of Regional Legislative Programs with Local Government Work Plans in Gorontalo, Indonesia. The thesis statement of the research is that the initial conditions, institutional design, leadership, and collaborative governance process will run optimally when institutional revitalisation is carried out between the Regional People's Representative Council and the Gorontalo Provincial Government so that it can achieve harmony between the main points of thought and the Regional Government Work Plan. The research method uses a qualitative approach. The results of the study show that between the Regional People's Representative Council and the Gorontalo Provincial Government have not established effective communication for the planning process, in this case there are different visions and goals to prioritize the interests of the community; aspects of Leadership, based on research findings that ineffective leadership has an impact on lack of integration between institutions, ineffective internal and external supervision, and weak collaboration between stakeholders; The collaboration process, in accordance with the findings of the research that there are political interests, sectoral ego, lack of effective coordination, lack of commitment, unclear direction and objectives, lack of monitoring and evaluation, lack of public understanding of the division of authority, disconnected communication between government units, lack of involvement of the Regional People's Representative Council in the Planning Process, and mismatch of goals between the Regional People's Representative Council and the Government Province so that the collaboration process has not been maximally achieved. Based on the research findings, in harmonising the Ideas of the Regional House of Representatives and the Regional Government Work Plan in Gorontalo Province, institutional revitalisation in collaborative governance is needed so that the initial conditions, institutional design, leadership and collaboration process between institutions can be achieved effectively.